Heart rhythm at hospital admission: A factor for survival and neurological outcome among ECPR recipients? - Rob, Daniel; Farkasovska, Klaudia; Kavalkova, Petra; Dusík, Milan; Havranek, Stepan; Pudil, Jan; Mockova, Eliska; Macoun, Jaromir; Belohlavek, Jan (Resuscitation, 2024)
BACKGROUND: The initial rhythm is a known predictor of survival in extracorporeal cardiopulmonary resuscitation (ECPR) patients. However, the effect of the rhythm at hospital admission on outcomes in these patients is less clear. METHODS: This observational, single-center study assessed the influence of the rhythm at hospital admission on 30-day survival and neurological outcomes at discharge in patients who underwent ECPR for out-of-hospital cardiac arrest (OHCA). RESULTS: Between January 2012 and December 2023, 1,219 OHCA patients were admitted, and 210 received ECPR. Of these, 196 patients were analyzed. The average age was 52.9 years (±13), with 80.6 % male. The median time to ECPR initiation was 61 min (IQR 54-72). Patients with ventricular fibrillation as both the initial and admission rhythm had the highest 30-day survival rate (52 %: 35/67), while those with asystole in both instances had the lowest (6 %: 1/17, log-rank p < 0.00001). After adjusting for age, sex, initial rhythm, resuscitation time, location, bystander, and witnessed status, asystole at admission was linked to higher 30-day mortality (OR 4.03, 95 % CI 1.49-12.38, p = 0.009) and worse neurological outcomes (Cerebral Performance Category 3-5) at discharge (OR 4.61, 95 % CI 1.49-17.62, p = 0.013). CONCLUSIONS: The rhythm at hospital admission affects ECPR outcomes. Patients presenting with and maintaining ventricular fibrillation have a higher chance of favorable neurological survival, whereas those presenting with or converting to asystole have poor outcomes. The rhythm at hospital admission appears to be a valuable criterion for deciding on ECPR initiation.
Keywords: Male; kardiopulmonální resuscitace; lidé středního věku; zástava srdce mimo nemocnici; Cardiac rhythm; Extracorporeal Membrane Oxygenation; srdeční frekvence; retrospektivní studie; Cardiopulmonary resuscitation; Extracorporeal membrane oxygenation; Out-of-Hospital Cardiac Arrest; míra přežití; příjem pacientů; Humans; Patient Admission; Cardiopulmonary Resuscitation; Heart arrest; Middle Aged; Survival Rate; Heart rhythm; senioři; hospitalizace; Ventricular Fibrillation; Cardiac arrest; mužské pohlaví; Female; Aged; Rhythm conversion; ženské pohlaví; Retrospective Studies; mimotělní membránová oxygenace; Heart Rate; Extracorporeal cardiopulmonary resuscitation; mozek; Adult; fibrilace komor; Hospitalization; Brain; dospělí; lidé